MM-Wave Planner Antenna For Wireless Communication (International Journal of Engineering and Computer Science, 2018)
The expectation of end users for and data allowance puts pressure on network operators in meeting demand and leads to requests from operators for access to greater amounts of spectrum. Making spectrum available to meet the future requirements of mobile broad band services is complex as prime spectrum for mobile broadband services is also access to services exhibiting increased speed heavily utilised by other services and is a scarce resource. Communications regulators must consider the impact on existing spectrum management arrangements and incumbent users. When making further spectrum available. Some of the issues to be taken into account ,